Universal Jurisdiction and International Obligations in Combating Terrorism: Legal Challenges and Case-Specific Analyses - Benjamin Okezie Kalu; Amarachukwu Onyinyechi Ijiomah (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2024)
This paper examines the concept of universal jurisdiction in combating international terrorism and the international obligations that arise from multilateral conventions, UN resolutions, and bilateral treaties. While doctrines like Aut Dedere Aut Judicare (prosecute or extradite) aim to ensure justice for crimes that transcend national borders, the implementation of these obligations often encounters legal and procedural hurdles within domestic legal frameworks. The paper provides empirical analyses of legal issues faced by law enforcement in the UK, Australia, New Zealand, and the US, particularly in sharing intelligence and providing mutual legal assistance in investigations, arrests, extraditions, and prosecutions in terrorism-related cases. It explores how differences in national legal systems, political factors, and human rights concerns—such as the admissibility of torture-obtained evidence and state-induced entrapment—complicate international cooperation. By analyzing case studies like Adham Hassoun, Guantanamo Bay, and others, the paper uncovers the intricate balance between complying with international obligations and navigating domestic legal constraints. Recommendations are made to harmonize international norms and enhance cooperation while safeguarding human rights in the global fight against terrorism